Dual-role of phosphonium – Based ionic liquid in epoxy/MWCNT systems: Electric, rheological behavior and electromagnetic interference shielding effectiveness. (November 2016) - Soares, Bluma G.; Riany, Nathan; Silva, Adriana A.; Barra, Guilherme M.O.; Livi, Sebastien
Graphical abstract: Highlights: Dual function of phosphonium ionic liquids: curing agent as well as dispersant aids. Epoxy-MWCNT-IL networks with good electrical properties and EMI shielding effectiveness. Influence of the dispersion procedure on the final properties. Abstract: Epoxy networks with improved electrical properties were prepared by using the non covalently functionalized multi-walled carbon nanotube (MWCNT) combined with phosphonium ionic liquid (IL). This IL exerts the function of dispersant aid for the MWCNT as well as curing agent of epoxy prepolymer. The influence of the mixing procedure on the dispersion of the MWCNT was evaluated by rheological behavior of the uncured mixtures and by transmission electron microscopy (TEM) of the cured epoxy systems. In fact, the dispersion of MWCNT within the IL is a key parameter to provide better dispersion, higher conductivity and storage modulus. Thus, the effect of the MWCNT content on the electrical and rheological percolation has been discussed. Moreover, the electromagnetic interference shielding effectiveness (EMI SE) of some systems have been also investigated.